PENERAPAN KUIS INTERAKTIF BERBASIS QUIZIZZ DALAM PEMBELAJARAN IPAS MURID KELAS VI SD NEGERI 4 KAWAN, KECAMATAN BANGLI, KABUPATEN BANGLI: Penelitian Kualitatif Deskriptip - Wahyu Dwipayana, I Kadek; Perni, Ni Nyoman; Herawan, Kadek Dedy (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the implementation of Quizizz-based interactive quizzes in IPAS learning for sixth-grade students at SD Negeri 4 Kawan, Bangli District, Bangli Regency. In addition, this study also aims to identify the obstacles faced during the implementation of Quizizz and the efforts made by teachers to overcome those obstacles. This study used a qualitative approach with a descriptive qualitative research design. The subjects of this study were the sixth-grade teacher and sixth-grade students of SD Negeri 4 Kawan. Data collection techniques were carried out through observation, interviews, documentation, and literature study. The data were analyzed through data reduction, data presentation, conclusion drawing, and verification. The results of the study showed that the implementation of Quizizz-based interactive quizzes in IPAS learning was carried out through the stages of preparation, implementation, and learning evaluation. Teachers used Quizizz as a learning medium to create a more interesting and enjoyable learning atmosphere. The use of Quizizz also helped students become more active and enthusiastic during the learning process. In its implementation, several obstacles were found, such as unstable internet connections, limited devices used by students, and the fact that some students were still unfamiliar with digital learning media. To overcome these obstacles, teachers provided guidance to students and adjusted the learning activities to classroom conditions. The implementation of Quizizz gave positive impacts on IPAS learning because it increased students’ participation, motivation, and interest in learning during the learning process.